Protein expression in mammalian cells : methods and protocols - Hartley, James L; Ed (Humana Press, 2012)
Through all of the recent progress provided by high throughput DNA sequencing technologies, it has become clearer and clearer that the study of proteins and protein organelles will be the key to unlocking our ability to manipulate cells and intervene in human disease. In Protein Expression in Mammalian Cells: Methods and Protocols, expert researchers in the field present a compendium of vital techniques to further our knowledge of mammalian protein expression. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips for troubleshooting and avoiding known pitfalls. Authoritative and concise, Protein Expression in Mammalian Cells: Methods and Protocols will aid scientists seeking to delve deeper into our own biology through the medium of other mammalian cells and proteins.